Neurophysiological effects of multiple mood episodes in bipolar disorder - Borgelt, Logan; Strakowski, Stephen M.; DelBello, Melissa P.; Weber, Wade; Eliassen, James C.; Komoroski, Richard A.; Chu, Wen‐Jang; Welge, Jeffrey A.; Blom, Thomas J.; Rummelhoff, Emily; Tallman, Maxwell; Lee, Jing‐Huei; et al. (Bipolar disorders, 2019)
Objectives Bipolar disorder is marked by progressive symptomatic changes, which have been linked with episode‐related structural findings—particularly in the prefrontal cortex. However, few studies have examined neurofunctional and neurochemical effects of disease burden. In this study, we compared first‐ and multi‐episode bipolar individuals. We hypothesized that the latter would demonstrate evidence of neurophysiological differences consistent with a model of progressive functional degradation of these networks. Methods First‐ and multi‐episode manic bipolar subjects participated in functional magnetic resonance imaging (fMRI) including a continuous performance task with emotional distractors, and in single‐voxel (1H) magnetic resonance spectroscopy (MRS). A priori fMRI regions‐of‐interest (ROI) included structures comprising prefrontal‐striatal‐amygdala networks; (1H)MRS voxels were placed within bilateral ventrolateral prefrontal (VLPFC) and anterior cingulate cortex (ACC). Both ROI and voxel‐based brain activation in response to emotional stimuli, and neurochemical concentrations derived from (1H)MRS were compared across bipolar groups. Results Multi‐episode bipolar subjects showed relatively lower regional activation across prefrontal‐striatal‐amygdala networks, including bilateral VLPFC, orbitofrontal cortex, ACC, putamen, caudate, and amygdala. Exploratory whole‐brain, voxel‐based analysis suggested additional areas of lower activation extending into Brodmann area 22, posterior parietal regions, and right thalamus. Glutamate and N‐acetylaspartate (NAA) concentrations were also relatively lower in the ACC of multi‐episode subjects. Conclusions Disease burden, exemplified by multiple affective episodes is associated with evidence of widespread decrements in affective network activity. Lower ACC NAA concentration is similarly consistent with a model of progressive functional deficits. These findings support the functional significance of previously observed progressive structural changes throughout these regions.